FPGA - based palm - print biometric system - features extraction and matching modules [electronic resource] - 192773 Soon, Boon Hooi; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Komputer)) - Universiti Teknologi Malaysia, 2007